2016
DOI: 10.1111/jth.13278
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant changes in fibrin clot structure in patients with cirrhosis are associated with oxidative modifications of fibrinogen

Abstract: To cite this article: Hugenholtz GCG, Macrae F, Adelmeijer J, Dulfer S, Porte RJ, Lisman T, Ari€ ens RAS. Procoagulant changes in fibrin clot structure in patients with cirrhosis are associated with oxidative modifications of fibrinogen. J Thromb Haemost 2016; 14: 1054-66. Essentials Patients with cirrhosis have hemostatic changes, which may contribute to a risk of thrombosis. This in vitro study compares clot formation and structure between patients and healthy subjects. Clot formation is delayed in patients;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 61 publications
(69 reference statements)
8
112
0
3
Order By: Relevance
“…We have recently shown that fibrin clot permeability in patients with cirrhosis of varying etiology is markedly reduced despite decreased fibrinogen plasma levels in these patients. The procoagulant properties of the fibrin clot in cirrhosis was attributed to increased oxidation of the fibrinogen molecule [24], which is known to result in a more thrombogenic fibrin clot. The thrombogenic nature of fibrin clots in patients with NAFLD, as identified in the present study, is likely attributable to multiple factors including increased oxidation of the fibrinogen molecule and elevated plasma fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that fibrin clot permeability in patients with cirrhosis of varying etiology is markedly reduced despite decreased fibrinogen plasma levels in these patients. The procoagulant properties of the fibrin clot in cirrhosis was attributed to increased oxidation of the fibrinogen molecule [24], which is known to result in a more thrombogenic fibrin clot. The thrombogenic nature of fibrin clots in patients with NAFLD, as identified in the present study, is likely attributable to multiple factors including increased oxidation of the fibrinogen molecule and elevated plasma fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…CT INT at admission was the only TE parameter that correlated with the development of bleeding events during hospitalization. The lack of association between hypocoagulable features on TE and the risk of bleeding observed in our study has also been reported by other authors and is probably due to the fact that portal hypertension constitutes the main pathogenic factor of bleeding events in cirrhosis. Hemostatic failure–related bleedings such as bruising, epistaxis, and gum bleeds are relatively infrequent and normally constitute minor events in the evolution of patients with decompensated cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin fiber density of each images stack were determined as previously described by Hugenholtz et al [35]. Briefly, lines were placed across the slices at 10 μm increments and averaging number of fibers intersecting the line were recorded.…”
Section: Methodsmentioning
confidence: 99%